Perception of Justice Regarding Direct Compensation and Its Impact on the Performance of Personnel Managers at Dinas Keuangan Angkatan Laut - Mahendra Pradana, Wendy (Dinasti International Journal of Digital Business Management, 2025)
Justice in direct compensation can be categorized into three main types: distributive justice, procedural justice, and interactional justice. The objective of this research is to understand the perceptions of personnel management staff at Dinas Keuangan Angkatan Laut regarding the justice of the direct compensation they receive and to analyze the impact of these justice perceptions on their motivation and performance. The method used in this research is qualitative descriptive. The findings indicate that transparency in policies, alignment between workload and compensation, and social comparison are key elements shaping employees' perceptions of fairness within the organization.